Antibacterial Activity of Seagrass Extract Against Pathogen Bacteria of Escherichia coli Strain Multi Drug Resistance (MDR) - Anma Hari Kusuma; Aditya Hikmat Nugraha; Ailsa Brinda Shasika (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Seagrass is a flowering plant that can adapt to the sea which has the potential to be used as an antibacterial. The purpose of this study to analyze seagrass extract as an antibacterial Escherichia coli strain Multi Drug Resistance (MDR). This research was conducted in May-July 2023. Seagrass samples came from the waters of Ketapang Beach, Pesawaran Regency, Lampung Province. The seagrass samples were meserated into three different solvents, namely methanol, n-hexane and ethyl acetate. Antibacterial test was carried out with scratch paper dripped with seagrass extract against E.coli bacteria colonies. The results obtained from the collection of seagrass samples found at Ketapang Beach contained four species, namely Enhalus acoroides, Cymodocea rotundata, Thalassia hemprichii and Halodule pinifolia. The highest yield of seagrass extract was found in E.acoroides with 14% methanol. The zone diameters of seagrass extracts against E.coli strain MDR were higher in seagrass extract H.pinifolia with n-hexana of 6,13 ± 3,27 mm. The conclusion of this research is that H.pinifolia seagrass extract using n-hexana solvent has potential as an antibacterial of E.coli strains Multi Drug Resistance (MDR).